Practical Flutter : Improve your Mobile Development with Google's Latest Open-Source SDK - Zammetti, Frank W. (Apress, 2019)
Explore what Flutter has to offer, where it came from, and where its going. Mobile development is progressing at a fast rate and with Flutter - an open-source mobile application development SDK created by Google - you can develop applications for Android and iOS, as well as Google Fuchsia. Learn to create three apps (a personal information manager, a chat system, and a game project) that you can install on your mobile devices and use for real. You will begin by getting a solid foundation of Flutter knowledge, and building on it immediately by constructing two more traditional productivity apps. You will also learn to create a game, enabling you to see a whole other perspective on what Flutter can do. In addition to building these apps, you'll have the benefit of reviewing real-world issues you might encounter, along with ways to deal with them through tips and tricks, all designed to make your Flutter experience that much more productive and, frankly, fun! Practical Flutter will leave you with a solid grasp of how to build apps with Flutter, and springboard into creating more advanced apps on your own. By the time your journey through this material concludes, another larger one will begin as you springboard, well-prepared, into the larger world of Flutter development, tackling any project that comes your way with aplomb. Practical Flutter is a learning adventure you won't want to miss.